MNX1 Promotes Malignant Progression of Cervical Cancer via Repressing the Transcription of p21cip1 - Zhu, Biqing; Wu, Yaqin; Luo, Jing; Zhang, Quanli; Huang, Jian; Li, Qian; Xu, Lin; Lu, Emei; Ren, Binhui (Frontiers in Oncology, 2020)
Motor neuron and pancreas homeobox 1 (MNX1) is a key developmental gene and has been found to be upregulated in several cancers. However, its biological role in cervical cancer remains largely unexplored. QRT-PCR, western blot and IHC showed that MNX1 was abnormally upregulated in cervical cancer tissues and cell lines. The high expression level of MNX1 correlated with poorer clinicopathologic characteristics in cervical cancer patients. Evaluated by RTCA (Real Time Cellular Analysis) proliferation assay, colony formation assay, EdU cell proliferation assay, transwell assay and matrigel assay, we found that knockdown of MNX1 inhibited proliferation, migration and invasion of cervical cancer in vitro, while overexpression of MNX1 promoted malignant phenotype of cervical cancer. And subcutaneous xenograft model confirmed the malignant phenotype of MNX1 in vivo. Furthermore, flow cytometry, chromatin immunoprecipitation and luciferase reporter assay indicated that MNX1 accelerated cell cycle transition by transcriptionally downregulating cyclin-dependent kinases p21cip1. In summary, our study revealed that MNX1 exerted an oncogenic role in cervical cancer via regulating cell cycle, especially by repressing the transcription of p21cip1. These results suggested that MNX1 might serve as a potential diagnostic marker and therapeutic target for cervical cancer patients.